2003
DOI: 10.1271/bbb.67.1194
|View full text |Cite
|
Sign up to set email alerts
|

UzuMutation in Barley (Hordeum vulgareL.) Reduces the Leaf Unrolling Response to Brassinolide

Abstract: A sensitive method to examine the brassinolide (BL) response of barley (Hordeum vulgare L.) using dark-grown leaf segments was established based on the known method for wheat. BL responses of 53 dwarf isogenic lines of barley were examined, and two lines were found having a uzu gene that doesn't respond significantly. These results indicate that uzu dwarfism may be caused by the non-responding character to BL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…As reported previously (Honda et al, 2003), we examined the leaf unrolling response of 53 isogenic barley cv Bowman dwarf lines and found that the response of two lines, both having the uzu gene, was lower than that of the normal line. To further deter- mine the response of the uzu line, we studied the unrolling response of uzu and normal lines to BL and t-Z using two isogenic line pairs of the uzu gene.…”
Section: Response Of Leaf Segments To Plant Hormonessupporting
confidence: 52%
“…As reported previously (Honda et al, 2003), we examined the leaf unrolling response of 53 isogenic barley cv Bowman dwarf lines and found that the response of two lines, both having the uzu gene, was lower than that of the normal line. To further deter- mine the response of the uzu line, we studied the unrolling response of uzu and normal lines to BL and t-Z using two isogenic line pairs of the uzu gene.…”
Section: Response Of Leaf Segments To Plant Hormonessupporting
confidence: 52%
“…In this test, both d61 and uzu did not respond to BRs Yamamuro et al, 2000). Honda et al (2003) reported that brh1 lines showed a slightly higher response than Bowman in this assay, and this finding was re-confirmed in this study ( Fig. 2A, Supplementary Fig.…”
Section: Physiological Characteristics Of Brh1supporting
confidence: 85%
“…, 2003). These plants have reduced sensitivity to brassinosteroids and provide a mechanism to introduce agronomically beneficial dwarfism in various barley cultivars (Honda et al. , 2003).…”
Section: The Bri1 Cladementioning
confidence: 99%